Topical Neck Cooling Without Systemic Hypothermia Attenuates Myocardial Ischemic Injury and Post-ischemic Reperfusion Injury - Zhang, Aimee; Rastogi, Radhika; Marsh, Katherine M.; Yang, Boris; Wu, Di; Kron, Irving L.; Yang, Zequan (Frontiers in Cardiovascular Medicine, 2022)
Background: Following acute myocardial infarction (MI), irreversible damage to the myocardium can only be reduced by shortening the duration between symptom onset and revascularization. While systemic hypothermia has shown promising results in slowing pre-revascularization myocardial damage, it is resource intensive and not conducive to prehospital initiation. We hypothesized that topical neck cooling (NC), an easily implemented therapy for en route transfer to definitive therapy, could similarly attenuate myocardial ischemia-reperfusion injury (IRI). Methods: Using an in vivo mouse model of myocardial IRI, moderate systemic hypothermia or NC was applied following left coronary artery (LCA) occlusion and subsequent reperfusion, at early, late, and post-reperfusion intervals. Vagotomy was performed after late NC in an additional group. Hearts were harvested to measure infarct size. Results: Both hypothermia treatments equally attenuated myocardial infarct size by 60% compared to control. The infarct-sparing effect of NC was temperature-dependent and timing-dependent. Vagotomy at the gastroesophageal junction abolished the infarct-sparing effect of late NC. Cardiac perfusate isolated following ischemia had significantly reduced cardiac troponin T, HMGB1, cell-free DNA, and interferon α and β levels after NC. Conclusions: Topical neck cooling attenuates myocardial IRI in a vagus nerve-dependent manner, with an effect comparable to that of systemic hypothermia. NC attenuated infarct size when applied during ischemia, with earlier initiation resulting in superior infarct sparing. This novel therapy exerts a cardioprotective effect without requiring significant change in core temperature and may be a promising practical strategy to attenuate myocardial damage while patients await definitive revascularization.